Pengaturan Pertanggungjawaban Pidana Korporasi di Indonesia - Mansyur (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2021)
The process of globalization and liberalization that occurs in all parts of the world, not only opens opportunities for businesses to play a direct role in the development of the world economy, but also contributed to the growth of various new crimes in the economic field, which are no less dangerous than other conventional crimes, because the impact is very large and has the potential to undermine the financial system and economy in a country or even the world economic system. The criminal acts that are rampant today related to the existence of the corporation are corporate criminal rampant acts which will have a serious and widespread impact, damage the joints of the life of the nation and threaten the stability of the country.Therefore, the law must take its role in creating justice and the welfare of the community and in handling it requires extraordinary ways, one of which is to make corporations the subject of criminal law which is considered capable of committing criminal acts and can be accounted for criminally. This type of research is normative legal research with the consideration that this research departs from the analysis of legislation. The approach method used in this study is the Law approach, conceptual approach, and case approach. The results of the study can be concluded that at this time the politics of corporate criminal liability regulation has not been able to realize corporate criminal liability. Therefore, reorientation and reformulation is needed in the policy of formulating corporate criminal liability that will come by emphasizing uniformity and consistency in determining when a criminal offense is said to be a criminal act of a corporation, who can be prosecuted and sentenced for criminal acts of the corporation, and what sanctions are appropriate for corporations that commit criminal acts. Keywords: Politics, Criminal Liability, Corporations